The Role of Social Media in the Dissemination of Information and Communication on Coronavirus Disease in Cameroon - Ndonko, Peguy (PT Keberlanjutan Strategis Indonesia, 2026)
Social media are being used more and more by the general public as a means of disseminating information between people. The outbreak of the coronas virus disease mobilized researchers in a variety of disciplines, as well as the governments of the countries affected by the pandemic. The digital media have played an important role not only in disseminating information, but also in communicating about the contamination, the spread and the preventive measures against this pandemic. This study, based on social science research methods and techniques, shows that social media have played an important role in disseminating information about the pandemic. The supply and demand for information took on a dizzying pace, helping to warn people about this new disease. Social media have helped to spread information about the corona virus as quickly as possible, but they have also enabled people to learn about the disease, the risks involved and how to prevent it, all of which is helping national governments with their public health programs.